2015
DOI: 10.1016/j.ijsu.2015.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shock wave therapy on glycosaminoglycan expression during bone healing

Abstract: ESWT stimulates of sulfated glycosaminoglycans during bone healing and enhanced early expression of HA compared to the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
4
0
4
Order By: Relevance
“…This appreciation completely changed when Wang et al 19,20 demonstrated that shockwaves generate upregulation and expression of various pro-angiogenic and pro-osteogenic growth factors, stimulating bone-healing. Basic research has shown that because of mechanical forces delivered by shockwaves to the cells and to the extracellular matrix, messengers are liberated and activate different genes and groups of genes in the cell nucleus 50,[136][137][138][139][140] . This phenomenon of biological conversion from a mechanical stimulus into electrochemical activity is called "mechanotransduction."…”
Section: Bone Disordersmentioning
confidence: 99%
“…This appreciation completely changed when Wang et al 19,20 demonstrated that shockwaves generate upregulation and expression of various pro-angiogenic and pro-osteogenic growth factors, stimulating bone-healing. Basic research has shown that because of mechanical forces delivered by shockwaves to the cells and to the extracellular matrix, messengers are liberated and activate different genes and groups of genes in the cell nucleus 50,[136][137][138][139][140] . This phenomenon of biological conversion from a mechanical stimulus into electrochemical activity is called "mechanotransduction."…”
Section: Bone Disordersmentioning
confidence: 99%
“…As a result, increased mineralization of the extracellular matrix (ECM) was observed on day 35 [ 23 , 24 ]. However, not only the mineralization of the ECM is stimulated by ESWT, but also increasingly sulfated glycosaminoglycans as main matrix components were observed during 28 days after shockwave exposure [25] . Not surprisingly, also components of the intracellular matrix (in particular actin stress fibers) are influenced in response to shockwaves and mTORC1 was alternatively localized subcellularly as vesicle-like inclusion on microfilaments [11] .…”
Section: Mechanism Of Shockwaves In Bone Tissue and Fracture Healingmentioning
confidence: 99%
“…Таким образом, в отличие от других подобных исследований [9], мы установили, что травма большеберцовой кости (дырчатый сквозной дефект метадиафиза) у кролей на 2-й день приводила к выраженному снижению содержания коллагена и ГАГ в регенератах на 29,1-32,6 % (р < 0,001), что мы связываем с катаболической фазой метаболической реакции организма на травму. В последующие сроки наблюдений (15, 30 и 45 дней), соответствующие анаболической фазе посттравматического периода, отмечено нормализацию показателей содержания коллагена и ГАГ в тканях регенератов обеих групп.…”
Section: результаты и их обсуждениеunclassified
“…Эффект стимулирования ЭУВТ синтеза сульфатированных ГАГ и гиалуроновой кислоты в регенератах посттравматических дефектов бедренных костей у крыс отметили в своих исследованиях P. R. Dias dos Santos и соавт. [9]. Однако эта гипотеза является дисскусионной, поскольку повышение содержания ГАГ и гиалуроновой кислоты в регенерате кости может носить вторичный характер за счет более интенсивного процесса костеобразования.…”
Section: результаты и их обсуждениеunclassified
See 1 more Smart Citation